Remineralization and anti-demineralization effect of orthodontic adhesives on enamel surrounding orthodontic brackets: a systematic review of in vitro studies - Kareem Hamdi; Ahmed Elsebaai; Mostafa A. Abdelshafi; Hamdi H. Hamama (BMC Oral Health)
Abstract Objective White spot lesions are initial sign of enamel caries that compromise esthetic appearance following orthodontic treatment. Thus, the systematic review was conducted to evaluate the remineralization potential of orthodontic adhesives on early-enamel lesions surrounding orthodontic bracket. Methods Search strategy was performed through three databases (PubMed, Web of Science, and Scopus). A total number of 1712 studies were identified for being potentially relevant, 62 among them were further assessed. Finally, 24 studies were included in this systematic review after adopting the eligibility criteria. The methodologies used to assess enamel remineralization were micro-computed tomography, cross-sectional microhardness, and polarized light microscopy for evaluating remineralization extent; surface microhardness, color change, and laser-induced fluorescence for evaluating superficial surface mineralization; Fourier Transform InfraRed, and Energy Dispersive Spectroscopy technique for chemical characterization. Results Bioactive glass (BAG), nano-hydroxyapatite (n-HAP), nano-amorphous calcium phosphate (n-ACP), nano-calcium fluoride (n-CaF2), fluorinated amorphous calcium phosphate nanoparticles (AFCP), and ammonium-based methacrylate monomer were incorporated into orthodontic adhesives. Seven out of the 24 included studies utilized commercially available orthodontic adhesives. While the remaining studies utilized experimental bioactive adhesives; 13 studies evaluated adhesives containing (BAG), two studies evaluated adhesives containing (n-ACP), one study evaluated adhesives containing (AFCP), and one study evaluated adhesives containing (n-HAP). Orthodontic adhesives containing the previously mentioned additives showed significant remineralization power compared to control group. Majority of studies that evaluated bioactive-based orthodontic adhesives revealed significant remineralization effect in comparison with their corresponding control groups. Out of 24 studies, 8 have assessed ion-release. However, few numbers of included studies evaluated the ion-release peak values. The output of most studies reported a significant increase of ion-release over time. Only one study reported a mark decrease of calcium and phosphate ions after 72 h. Following the high risk of bias in the majority of studies, and lack of standard evaluation protocol, meta-analysis was not conducted. Conclusion The outcome of the included studies supports the effectiveness of incorporation of remineralizing agents into orthodontic adhesives.